1998
DOI: 10.1046/j.1365-2362.1998.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of iron metabolism in the acute‐phase response: interferon γ and tumour necrosis factor α induce hypoferraemia, ferritin production and a decrease in circulating transferrin receptors in cancer patients

Abstract: Our data point to a central role for the cytokine network in the modulation of iron metabolism in the acute-phase response and anaemia of chronic disease. TNF, possibly via induction of IL-6, and IFN-gamma induce hypoferraemia, which may in part result from a decrease in tissue iron release based on a primary stimulation of ferritin synthesis. The fall in sTfR levels may reflect an impaired erythroid growth and/or TfR expression mediated by TNF and IFN-gamma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
2
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 54 publications
5
129
2
4
Order By: Relevance
“…However, after 6 h the IL-6 was decreased as compared with the value 1 h earlier. This is in accordance with the results of earlier studies, which indicate that IL-6 level begins to decline somewhere between 4 and 8 h after the onset of infection/inflammation (Meffert et al, 1994;Berger et al, 1997;Feelders et al, 1998).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, after 6 h the IL-6 was decreased as compared with the value 1 h earlier. This is in accordance with the results of earlier studies, which indicate that IL-6 level begins to decline somewhere between 4 and 8 h after the onset of infection/inflammation (Meffert et al, 1994;Berger et al, 1997;Feelders et al, 1998).…”
Section: Resultssupporting
confidence: 93%
“…Despite an alteration in the other iron parameters the S-ferritin level remained constant throughout the day (51.870.8 mg/l, mean7s.e.m. ), probably owing to the previously reported delay in the alteration of ferritin kinetic (Feelders et al, 1998;Kemna et al, 2005).…”
Section: Resultsmentioning
confidence: 86%
“…A better alternative to CRP is thought to be AGP, which remains elevated for a longer duration of time. One time course study that followed changes in concentration of multiple APPs and iron status measurements, found that SF concentrations rose steadily reaching a peak, like CRP, at day 2, but like AGP, remained elevated for several subsequent days (Feelders et al, 1998). It is because of this extended period of elevation in SF and AGP that AGP is thought to better reflect the changes in SF that accompany the APR.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inflammation/infection can be accompanied by decreased Hb and increased ferritin. CRP rises rapidly in response to inflammation and decreases toward normal within 36-48 hr, whereas both ferritin and AGP may remain elevated for as long as 5-10 days after the onset of an acute inflammatory response [34,35]. Lead concentrations above 15-18 mg/dl can impair red cell production, reflected in elevated FEP values [36].…”
Section: Methodsmentioning
confidence: 99%